2017
DOI: 10.1038/s41467-017-00888-8
|View full text |Cite
|
Sign up to set email alerts
|

Stapled peptide inhibitors of RAB25 target context-specific phenotypes in cancer

Abstract: Recent evidence has established a role for the small GTPase RAB25, as well as related effector proteins, in enacting both pro-oncogenic and anti-oncogenic phenotypes in specific cellular contexts. Here we report the development of all-hydrocarbon stabilized peptides derived from the RAB-binding FIP-family of proteins to target RAB25. Relative to unmodified peptides, optimized stapled peptides exhibit increased structural stability, binding affinity, cell permeability, and inhibition of RAB25:FIP complex format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…In contrast, Rab25 is known to function as an oncogene in ovarian and luminal breast cancers . Indeed, treatment with a stapled peptide, which inhibits interactions between Rab25 and its effectors, suppresses the proliferation and migration of ovarian cancer cells in which Rab25 functions as an oncogene, but augments the aggressive phenotype in breast cancer cells in which Rab25 functions as a tumor suppressor . Furthermore, Jeong et al found that the oncogenic activity of Rab25 in ovarian cancer cell lines accrued through Rab25‐dependent increases in β1 integrin levels, which subsequently activated EGFR, upregulated VEGF‐A expression, and increased Snail expression, ultimately promoting cancer cell invasion .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Rab25 is known to function as an oncogene in ovarian and luminal breast cancers . Indeed, treatment with a stapled peptide, which inhibits interactions between Rab25 and its effectors, suppresses the proliferation and migration of ovarian cancer cells in which Rab25 functions as an oncogene, but augments the aggressive phenotype in breast cancer cells in which Rab25 functions as a tumor suppressor . Furthermore, Jeong et al found that the oncogenic activity of Rab25 in ovarian cancer cell lines accrued through Rab25‐dependent increases in β1 integrin levels, which subsequently activated EGFR, upregulated VEGF‐A expression, and increased Snail expression, ultimately promoting cancer cell invasion .…”
Section: Discussionmentioning
confidence: 99%
“…Both Rab11A and Rab11B are mutated in developmental disorders, with putative inactivating Rab11A or Rab11B mutations leading to intellectual disability and brain malformation 16 , 17 . Overexpression of Rab25 has been implicated in poor prognosis in ovarian cancer, with stapled peptide inhibitors of Rab25-effector binding inhibiting migration and proliferation 18 , 19 . Many intracellular pathogens, including viruses 20 , bacteria 21 , and parasites 22 subvert membrane trafficking through targeting Rab11-positive vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Since these molecules have the benefits of oral bio-availability, efficiency and shortened half-life activity [ 117 ], they are often preferred over large molecules for the treatment of diseases. Previous studies have shown that small GTPases, particularly Rab, Rho and Ras from the Ras superfamily, can be regulated by small molecules that interferes with the protein functions in numerous ways such as interfering with the interaction between small-GTPases and GEF [ 118 ][ 119 ], inhibiting through covalent modification [ 120 ], interfering with the interaction between GTPase and effector[ 35 ][ 121 ][ 122 ], blocking membrane recruitment by inhibiting protein prenylation[ 123 ][ 124 ], etc. However, designing competitive small molecule inhibitors that binds to the nucleotide binding site of small GTPases is challenging since these proteins have high affinity for the nucleotide [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first inhibitor designed to regulate the Rab proteins was'CID1067700', which targets the active site of Rab7[ 34 ]. Later design of a Rab25 modulator was a stapled peptide 'RFP14' that selectively blocks the interaction between Rab25 and its effectors, by mimicking a common interaction motif present in the effectors[ 35 ].To design an effective therapeutic strategy for regulating a protein, it is necessary to identify druggable sites/regions/pockets on the protein surface, where small molecules can bind to and modulate the aberrant protein function [ 36 ][ 37 ]. Some binding pockets on the protein surface may be formed transiently and are often not revealed in a single static structure of the protein resolved using methods such as X-ray crystallography [ 38 ][ 37 ].…”
Section: Introductionmentioning
confidence: 99%